THE INVESTIGATION OF THE CLASSICAL CEPHEID RT Aur PERIOD - Kosinsky, A. S.; Tamello, V. G.; Kushmar, I. J.; Bryukhanov, I. S.; Semenyuta, A. S.; Balyuk, I. I. (Одеські астрономічні публікації, 2017)
The outcomes of the research into RT Aur period for the last 93 years are given in the article. New elements of changes in RT Aur brightness have been determined by the authors: J.D.max=2447890,265+3.7283116*E.